MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI MELALUI MEDIA PUZZLE BERBASIS TRI HITA KARANA DI TK PRA WIDYA DHARMA BELANCAN KECAMATAN KINTAMANI KABUPATEN BANGLI - Widnyani Ni Nyoman; Srie Kusuma Wardhani Ni Ketut; Luwih I Made (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Cognitive development is the basis for a child's ability to think, be creative. The ability to think of children can be seen when children can solve simple problems that, recognize colors, recognize various objects and shapes. However, many young children still cannot recognize various kinds of objects around them, recognize colors, and recognize shapes. Puzzle media is a game that compiles a picture or object that has been broken into intact image form. The dismantling of the game, makes children think so that their (cognitive) knowledge develops. Children will use their thinking power to find puzzle media pieces and arrange them into an image a form complete. Through a puzzle media based on Tri Hita Karana, it is used as of planting Hindu religious teachings be taught from an early age. Tri Hita Karana is the three causes of happiness that teach humans to build a harmonious relationship with God, fellow humans and their environment. The problems that will be discussed include : (1) How is the process of implementing learning in improving early childhood cognitive abilities through the Tri Hita Karana-based puzzle media at TK Pra Widya Dharma Belancan? (2) What are the obstacles a teacher in improving early childhood cognitive abilities through the Tri Hita Karana-based puzzle media at TK Pra Widya Dharma Belancan? (3) What are the efforts made by the teacher to overcome problems in improving early childhood cognitive abilities through the Tri Hita Karana-based puzzle media at TK Pra Widya Dharma Belancan?. The theories used to analyze the formulation of the problem are Jhon Watson's theory of behaviorism, Piaget's cognitive theory, and Lev Vygotsky's theory of constructivism. The subjects in this study were teachers, school principals, and children who attend TK Pra Widya Dharma Belancan. Methods of data collection through non-participant observation, structured interviews, document study and literature study. The collected data were analyzed by using the qualitative descriptive analysis method with data reduction, data presentation and conclusion drawing. The results showed (1) The process of implementing the Tri Hita Karana based puzzle media in improving children's cognitive abilities is divided into two stages, namely the planning stage and the implementation stage, (2) the constraints faced by the teacher during the application process of the Tri Hita Karana based puzzle media in improving children's cognitive abilities are divided into two factors, namely internal factors and external factors, (3) the efforts made by the teacher in overcoming the obstacles of implementing Tri Hita Karana based puzzle media in improving children's cognitive abilities, namely by improving the quality of learning including making attractive media, create their puzzle media, and motivate children to learn by giving gifts and praise. (3) the efforts made by the teacher in overcoming the obstacles of implementing Tri Hita Karana based puzzle media in improving children's cognitive abilities, namely by improving the quality of learning including making attractive media, creating their puzzle media, and motivating children to learn by giving gifts and praise